Educational Programmes, Rehabilitation and Management of Juvenile Delinquents in Lagos State Juvenile Homes, Nigeria - Fashiku Christopher Oluwatoyin (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study to examined the influence of educational programmes on the rehabilitation and management of juvenile delinquents in Lagos State juvenile homes. The study adopted the descriptive survey research design. The population for the study comprised a total of 332 people. Simple random sampling technique was used to select 20 juveniles from each of the juvenile homes. The managers and members of staff of the two selected juvenile homes were selected using total enumeration sampling technique and this made a total of two managers and 33 members of staff. Three research instruments were used to collect data for the study. (i) An interview guide titled “Rehabilitation of Juvenile Delinquents” (RJD) (ii) An interview guide titled “Management of Educational Programmes in Juvenile Homes” (MEPJH) (iii) A questionnaire on the “Influence of Educational Programmes on Rehabilitation of Juvenile Delinquents” Percentage scores and Analysis of Variance (ANOVA) were used to analyse the data collected. Results showed that majority of the respondents 77.5% alluded that educational programmes were made available at the juvenile homes also, 55% said that academic, counselling and vocational education were the only educational programmes available at the homes. Respondents claimed that the juvenile homes were managed by the Lagos State Ministry of Youth and Social Development, the educational programmes and teacher recruitment were handled by the State Ministry of Education. The study concluded that educational programmes had positive and very notable influence on the rehabilitation of juvenile delinquents in Lagos State juvenile correctional homes. Based on the findings of this research, it was recommended among others that: Literacy and life skills training should be included as part of educational programmes in the juvenile homes. Expansion of available accommodation facilities to cater for current population of juveniles and also future increase and that in the Juvenile homes, the children offenders should be separated from those who have not committed offenses, those who are just in need of care and protection.